Pengaruh Harga, Lokasi, Kualitas Pelayanan dan kualitas Produk terhadap Kepuasan Konsumen pada Percetakan Maskumambang Kediri - Krisna Pramudia Putra Wibowo; Ustadus Sholihin; Beny Mahyudi Saputra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The study aims to determine the effect of price, location, service quality, and product quality on consumer satisfaction in printing maskumambang kediri. The sample in this study amounted to 80 consumers who had made purchases at the Kediri maskumambang printing house. The sampling technique uses accidental sampling. This research uses quantitative methods which are then processed using SPSS. The results showed that price affects consumer satisfaction, location does not affect consumer satisfaction, service quality affects consumer satisfaction, product quality affects consumer satisfaction. Price, Location, Service Quality, and Product Quality jointly affect Consumer Satisfaction.